Qiqi cookies cookies - Mohd Ghazali, Muhamad Kusyairi; Azman, Muhammad Lutfi; Sidek Omar, Ayuni Mardhiyyah; Mohamad, Fatiha (2020)
Qiqi cookies is a company that produces and provides cookies, one of Malaysian favourite cookies with healthiest and many types of cookies. Qiqi cookies is offering walk in shop and deliveries to nearby areas. Not to forget, Qiqi cookies also provides post services but will keep ensuring the quality of the products until it meets the customers who lives outside Sungai Petani,Kedah. Qiqi cookies has highly potential as the shop is located in central of Sungai Petani .Sungai city has been popular among people who pays a visit there,so Qiqi cookies takes chances to produce and sell products there.The close proximity of Sungai Petani,Kedah to the major landmarks make it an ideal location for a new enterprise business.Therefore this company handled and managed by Muhamad Kusyairi bin Mohd Ghazali as the General Manager (GM) with helps of other workers such as marketing manager,finance manager and kitchen crews. Qiqi cookies wants to be outstanding as other cookies company,such as Munchy Food Industries SDN BHD, Morning-Star Food Industry (M) Sdn Bhd and SGK Food Industry SDN. BHD.Qiqi cookies will focus on cookies compared other company which is focus on frozen food and fine foods.The profitability of Qiqi cookies is higher as the price offered is cheaper to other shops.Hence, Qiqi cookies will produce more types of cookies in the future in order to catch customers’ attention and can increase sales indirectly.